Odontoma pada anjing Siberian Husky - Muhamad Arfan Lesmana; Ulvi Hudriyah; Albiruni Haryo; Fathinah Inas Hutasuhut (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2020)
A 12-year-old female Siberian Husky dog ​​was taken to the Animal Education Hospital, Faculty of Veterinary Medicine, Universitas Brawijaya with complaints of meat or mass in the gum area, this has been going on for ± 1 month, but the dog still wants to eat. Physical examination found that the dog's body temperature was 38.9 ºC and heart rate 100 x/minute, and found a medium-sized mass in the gums, there are a lot of tartar and bad breath. Radiographic examination results showed the presence of radioopacity of the mandibular dexter region. The results of blood tests show leukocytosis, lymphocytosis and monocytosis are indications of inflammation. The diagnosis of this patient's disease is odontoma. Therapy is carried out by surgical action of mass extirpation, extraction of the surrounding teeth and cleaning of tartar. Post-surgery given antiseptics, corticosteroids and supplements, and dogs are allowed to go home after 1 day of post-surgical treatment because the condition has improved.